How to Govern the enlarged European Union? - Zielonka, J (Routledge, 2009)
Argues that the hierarchical mode of governance has been rendered inadequate by enlargement and the EU should embrace more flexible, decentralised and soft modes of governance. Considers the complex relations between new member states such as Poland with their neighbours, and their opposition to strong centralisation of European foreign and security policies. Argues that if the existing, much-cricitized system for adopting foreign and security policies prevents the EU from becoming a global actor in these fields (with quick decision-making and rapid responses), it nevertheless creates conditions for deliberation and prevents the EU rushing to ill-conceived courses of action.